2011
DOI: 10.1111/j.1439-0396.2011.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the pro‐inflammatory NF‐κB pathway by a grape seed and grape marc meal extract in intestinal epithelial cells

Abstract: In pigs and other monogastric animal, the weaning phase is commonly accompanied by an increased susceptibility to gut disorders such as diarrhoea owing to the induction of an inflammatory process in the intestine during weaning. Given the unfavourable effects of intestinal inflammation on feed consumption, digestive capacity of the intestine and growth of animals, controlling intestinal inflammation is a reasonable approach for the maintenance of performance characteristics of livestock animals. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 41 publications
3
30
1
1
Order By: Relevance
“…Interestingly, this wine extract induced miR-126, a microRNA that is involved in negative regulation of vascular cell adhesion molecule-1 expression [66]. CaCo-2 cells treated with TNF-α confirmed the anti-inflammatory effect of grape seeds and of grape marc meal-based feed additives used for livestock nutrition, in that they inhibited NF-κB transactivation and IL-1β, IL-8, monocyte chemotactic protein-1, chemokine CXC ligand 1 expression [67].…”
Section: Effects Of Wine On Intestinal Damagementioning
confidence: 69%
“…Interestingly, this wine extract induced miR-126, a microRNA that is involved in negative regulation of vascular cell adhesion molecule-1 expression [66]. CaCo-2 cells treated with TNF-α confirmed the anti-inflammatory effect of grape seeds and of grape marc meal-based feed additives used for livestock nutrition, in that they inhibited NF-κB transactivation and IL-1β, IL-8, monocyte chemotactic protein-1, chemokine CXC ligand 1 expression [67].…”
Section: Effects Of Wine On Intestinal Damagementioning
confidence: 69%
“…Previous in vitro studies showed a similar inhibitory effect of polyphenols in human cells (Williamson et al, 2006) and in murine splenocytes (Yamanaka et al, 2012). In addition, Gessner et al (2012) found antiinflammatory effects of phenolic compounds extracted from grape seeds and grape marc in intestinal cells under in vitro conditions. Conversely, lymphocyte-derived cytokines increased in serum samples of calves fed polyphenols extracted from pomegranate, thus showing an immune-stimulatory effect (Oliveira et al 2010).…”
Section: Immunological Determinationsmentioning
confidence: 80%
“…Os polifenóis do vinho parecem modular a atividade do AP-1 por meio da inibição da PKC, da via MAPK e/ ou alterando a ligação do AP-1 ao DNA. Gessner et al (2012) constatatam que o efeito anti-inflamatório de extratos obtidos de farinhas de semente e de bagaço de uva também ocorre via inibição da via NF-kB. Em macrófagos humanos com inflamação mediada pelo LPS, extratos de uva (Vitis labrusca) em pó (GPE) atenuaram a fosforilação da JNK e p38 e diminuíram a degradação do IkBá e a fosforilação da c-Jun, bem como bloquearam o NF-kB.…”
Section: Mecanismos Moleculares De Ação De Polifenóis De Uvas E Vinhounclassified